Traders, the AmaXhosa and the Colonists - Snodgrass, Margaret (Toposcope, 2020)
In the early years of the eighteenth century, the Dutch were the first colonists to trade with the Xhosa. By 1752 there was a substantial trade in ivory and by 1770 a well-beaten wagon road into Xhosaland. Copper, iron and beads from the Colony were exchanged for cattle and ivory. The Dutch farmers (Boers) it seems were hunters of the elephants rather than ivory traders. A Boer would give a chief a present in exchange for permission to hunt in his territory. The chief in turn would provide guides to show the hunter where to find the elephants.